Investigating Kurdish EFL Learners’ Preferences to Oral Corrective Feedback at College Level (Raparin Journal of Humanities (RJH), 2026)
This study aims to investigate Kurdish EFL learners’ preferences to oral corrective feedback (OCF) and any differences between Kurdish EFL learners’ preferences to OCF strategies based on gender. It was carried out at four different departments of English in Duhok city. The participants of the study were 104 Kurdish EFL learners; 52 males and 52 females. A quantitative research methodology was used to conduct the study. Survey questionnaires were used to collect data from learners and SPSS program (version 26) was used to analyze the data collected from questionnaires. The results revealed that after finishing from speaking was the most preferred timing of correction among the participants. Regarding types of spoken errors and OCF strategies, participants mostly preferred the correction of serious spoken errors and metalinguistic explanation was the most preferred strategy. In addition, the results revealed that there were some gender differences in Kurdish EFL learners’ preferences to OCF strategies. The implications of the study’s findings will be of great significance to teachers, teacher training programs and curriculum designers where they highlight the importance of tailoring OCF and incorporating certain teaching methods based on learners’ preferences and gender. Furthermore, it suggests the employment of qualitative methodologies and inclusion of other variables in order to have a better understanding of the study.